Spotlight on ORNAC Members: AN INTERVIEW WITH CHRIS MULFORD, RN, BSC (HONS) NURSING, CPN(C) - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2012)
Chris Mulford, RN, BSc (Hons) Nursing, CPN(C), is a Perioperative Registered Nurse working as the Clinical Resource Leader in the Operating Rooms and Endoscopy departments at The Scarborough Hospital (TSH) in Scarborough, ON. Chris became a perioperative nurse in Scotland in 2003 and subsequently immigrated to Canada, in October 2005, in order to advance his perioperative nursing career. Chris currently resides in Whitby, ON, with his wife and two boys, and sits on the periOperative Registered Nurses of Greater Toronto (ORNGT) Executive as its Secretary. Chris received his Baccalaureate, with honours in Nursing, from the Robert Gordon University in Aberdeen, Scotland, in 2003, and successfully completed his Perioperative Certification with the CNA in 2011.